The Study of Stimulated Visual Behaviour Related to Nonverbal Communication. (2015) - Gabor, Dan; Baritz, Mihaela; Repanovici, Angela
Abstract: Any form of emotional behaviour manifests through the adjustment of physiological acts of some components from the globe of the eye. Thus, the systemic analysis of these adjustments through different methods allows the establishment of some connections between the level of emotional state and non-verbal communication. The research that is the object of this article is based on the biomechanics analysis of the binocular vision and on the correlation of means to make a visual and a non-verbal expression, with a degree of visual stimulation respectively (through chromatic, illumination, movement, form and sizes). The analysis methodology is based on the data collection from the stimulation procedures of the visual system and following the physiological reactions of the subjects from the target group. Thus, the dynamic stimulation strategies for the visual system and the tracking of the physiological reactions of the subjects from the target group are being applied. Consequently, the dynamic stimulation strategies of the visual system are being applied, in order to follow the reactions of the visual behaviour. The results obtained are analyzed through correlative methods and are being processed through image processing methods, in order to highlight the interdependency relations between the stimuli and communication. An important aspect taken from the experimental researches is highlighter from the correlative analysis through computerized methods. Also, the final results are materialized through the fast and objective determination of the reporting coefficient -stimulus/behavioural answer (RC-S/BA).